Prevalence of hypertension, levels of lipids and blood glucose in patients with acute pancreatitis, chronic pancreatitis and pancreatic cancer - I. N. Grigorieva; O. V. Efimova; T. S. Suvorova; N. L. Tov; T. I. Romanova (Российский кардиологический журнал, 2020)
Aim. To determine the prevalence of hypertension (HTN) in patients with acute pancreatitis (AP), chronic pancreatitis (CP), pancreatic cancer (PC) and establish associations of HTN with other risk factors (obesity, dyslipidemia (DLP), plasma glucose ≥7,0 mmol/l, smoking, alcohol consumption).Material and methods. This observational multicenter clinical cross-sectional uncontrolled study included 44 patients with AP, 97 patients with CP and 45 patients with PC. The groups were comparable by sex and age. The HTN was diagnosed according to the criteria of Russian Society of Cardiology (2020).Results. HTN was much more common in patients with PC (55,6%) than in patients with AP (25,0%) (χ 2 =8,6, p=0,003). In patients with CP, the prevalence of HTN (39,2%) did not differ from those with AP or PC. Among patients with AP and HTN, higher levels of triglycerides (TG) (U=88,0, p=0,010) and glucose (U=89,5, p=0,011) than in non-HTN patients with AP were determined. In HTN patients with CP, glucose ≥7,0 mmol/l was recorded 3 times more often than in non-HTN patients with CP (χ 2 =16,2, p=0,000). In patients with PC and HTN, a higher mean body mass index (BMI) (F=7,8, p=0,008) and less common normal body weight than in non-HTN patients with PC (28,0 and 65,0%, χ 2 =6,2, p=0,013) was revealed. In patients with CP, increased glucose levels by 1 mmol/l (Exp (B)=1,933, 95% confidence interval (CI) 1,350-2,767, p=0,000) or BMI by 1 kg/m2 (Exp (B)=1,224, 95% CI 1,085-1,380, p=0,001) raised the probability of HTN; in patients with PC, increased BMI by 1 kg/ m2 (Exp (B)=1,394, 95% CI 1,057-1,840, p=0,019) or age by 1 year (Exp (B)=1,251, 95% CI 1,052-1,489, p=0,011) raised the probability of HTN.Conclusion. HTN was more often observed in patients with PC than in those with AP. In patients with CP, the prevalence of HTN did not differ from those with AP or PC. HTN was a cofactor to other metabolic risk factors (glucose ≥7,0 mmol/l, obesity) in patients with AP or CP; behavioral risk factors, on the contrary, were less common in HTN patients with AP or CP. In patients with CP, there was a direct association of HTN with glucose levels or BMI, and in patients with PC — HTN with BMI or age.